PRELIMINARY DATA ON THE PROPHYLAXIS OF SEVERE FORMS OF COVID-19 THROUGH EXERCISE - Bogdan-Alexandru HAGIU; Iulian Dumitru TURCULEȚ; Iulian Marius DUMITRU (Cluj University Press, 2021)
Independent studies suggest the possibility of prophylaxis of severe forms of COVID-19 through moderate-intensity exercise. There is the fear that intense exercise could increase the risk of the virus entering the cell, a determining factor being hypoxia. As a result, in this paper we aimed to assess the heart rate and oxygen saturation of the blood in the case of Kangoo Jumps and aerobic training at home. Kangoo Jumps workouts practiced in such a way as to avoid in principle the high intensity of the effort, do not produce transient hypoxia, not even in subjects whose heart rate indicated an intense effort. Preliminary data show that aerobics at home does not produce hypoxia in mature adults and the elderly, and heart rates do not exceed the limit of moderate intensity; however, additional studies are required for both categories of exercises under study. REZUMAT. Date preliminare privind profilaxia formelor grave de covid-19 prin exerciții fizice. Studii independente sugerează posibilitatea profilaxiei formelor severe de COVID-19 prin exerciții de intensitate moderată. Există teama că exercițiile intense ar putea crește riscul pătrunderii virusului în celulă, un factor determinant fiind hipoxia. În consecință, în această lucrare ne-am propus să evaluăm frecvența cardiacă și saturația de oxigen a sângelui în cazul Kangoo Jumps și antrenamentului aerob la domiciliu. Antrenamentele Kangoo Jumps practicate în așa fel încât să evite în principiu intensitatea ridicată a efortului, nu produc hipoxie tranzitorie, nici măcar la subiecții a căror frecvență cardiacă a indicat un efort intens. Datele preliminare arată că aerobicul la domiciliu nu produce hipoxie la adulții maturi și vârstnici, iar ritmul cardiac nu depășește limita intensității moderate; cu toate acestea, sunt necesare studii suplimentare pentru ambele categorii de exerciții discutate în acest studiu. Cuvinte cheie: COVID-19, Kangoo Jumps, aerobic.